Penyadapan dalam Hukum Internasional dan Implikasinya terhadap Hubungan Diplomatik Indonesia dengan Australia - Jawahir Thontowi (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The first and foremost issue in this study is the general principles and legal arrangements of tapping into national and international human rights law. Second, as lex specially can tappin be prosecuted to national or international law? Third, why is the wiretapping of Australia against Indonesia not considered as a crime but a violation of the diplomatic code of conduct. This is a normative research. The study reveals that first: legally tapping is prohibited by law and international human rights based on the Universal Declaration of Human Rights (UDHR) in 1948, the International Covenant on Civil and Political Rights (ICCPR) in 1966, the European Convention for the Protection of Human Rights and Fundamental Freedoms (1958) and the 1961 Vienna Convention. While in the national law, the prohibition of tapping is provided in Article 28G paragraph (1) of the 1945 Constitution, Article 32 of law No. 39 of 1999, Article 40 of Law No. 36 of 1999, Article 31 paragraph (1) of Law No. 11 of 2008, and Article 31 paragraph (2) of Law No. 11 Year 2008. Tapping is allowed when the order and security of the country is being threatened as stipulated in the Law on Combating Criminal Acts of Terrorism, Narcotics Law, the Law on the Corruption Eradication Commission, and the Law on State Intelligence. Second, the ban on wiretapping in international criminal law can be excluded for particular crimes as stipulated by Rome Statute of 1998, and Transnational Organized Crime. Thirdly, in the context of the behavior relations between countries, Australia tapping against Indonesia has shifted meaning from a crime  into a violation of the diplomatic code of conduct. Indonesia acted diplomatically towards Australia’s violation by forgiveness.